EXAMINING INDONESIAN TOURISTS' OUTLOOK ON RURAL TOURISM: QUALITATIVE ANALYSIS OF SERVQUAL AND E-SERVQUAL DIMENSIONS - Mochammad Jibril; Daniel Tumpal Hamonangan Aruan (UPT Publikasi Ilmiah UNISBA, 2024)
This research aims to explore the role of digital transformation in enhancing the rural tourism industry through PT. Teknologi Pandu Wisata (Pandooin). It focuses on utilizing consumer preferences to improve the quality of tourism products, the role of marketplaces in enhancing online purchase intention, and evaluating custom itinerary features on customer satisfaction. Additionally, the study contributes to the development of SERVQUAL and E-SERVQUAL theories by exploring new dimensions, including security and additional services such as travel documentation, as well as website flexibility. By employing a qualitative approach through in-depth interviews and triangulating data from various sources, this research is expected to provide relevant and holistic insights into the role of digitalization in improving the quality of rural tourism.